(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
The present study aimed to isolate some proteins from placenta of Mongolian mares and measure their concentrations using ELISA test kits. In order to achieve this aim, a total of 12 variants of protein isolation experiments in triplicates were performed to isolate proteins from each homogenates, which were obtained with 3 methods of tissue homogenizations of placental tissue of Mongolian mare using distilled water, phosphate buffer saline and Tris-HCl, by use of 4 methods of protein extraction and precipitation with distilled water, sulfate ammonium salt and organic solvents such as ethanol and acetone. Molecular weights of proteins isolated using above variants of methods or a total of 36 samples determined by SDS polyacrylamide gel electrophoresis demonstrated the bands of proteins with molecular weights ranging from 1,060 to 26,600 dalton were clearly detected on the electrophoregram, and 1083.9 to 5747.2 μg/ml total proteins in all samples were measured by Pierce BCA assay kit. Results of ELISA measurements of placental protein 13 (PP13) and placental growth factor (PlGF) in samples that PP13 and PlGF concentrations in both extracts, one of which were homogenized in PBS, followed by ethanol precipitation and another, homogenized in distilled water, followed by acetone precipitation were 34.4±9.2 and 34.9±1.3 pg/ml and 469.4±46.9 and 404.7±153.9 pg/ml respectively demonstrated extracts containing higher amounts of biologically active proteins can be obtained by using methods of homogenization of tissues extracted in PBS or distilled water and precipitation with organic solvents. Монгол гүүний эхэсийн ханд бэлтгэж, өсөлтийн хүчин зүйл, 13-р уураг тодорхойлсон дүн Хураангуй: Энэ судалгааны ажлын зорилго нь монгол гүүний эхсийн зарим уургийг ялган авч, ЭЛИЗА-ийн аргаар тодорхойлох явдал байв. Энэхүү зорилгын хүрээнд Монгол гүүний эхсийн эдийг нэрмэл ус, фосфатын буфер, трис-давсны хүчлээр хандлан гомогенжүүлэх 3 аргыг ашиглан, тэдгээрээс гарсан гомогенат тус бүрээс уураг ялгах туршилтыг сульфат аммоний давс, этанол, ацетоноор тундасжуулах, нэрмэл усанд хандлах 4 янзын аргаар уураг ялгасан нийт 12 хувилбарыг тус бүр 3 давталттай хийсэн юм. Дээрх хувилбаруудаар ялган авсан уургууд буюу нийт 36 дээжинд молекул жинг электрофорезийн аргаар тодорхойлоход ихэнх хувилбаруудад 1,060-26,600 дальтон жинтэй уургийн толбууд тод илэрч байсан ба уургийн хэмжээг Пьерсийн цомгоор тодорхойлоход 1083.9-5747.2 мкг/мл уураг илэрсэн юм. Эхсийн өвөрмөц 13-р уураг, эхсийн өсөлтийн хүчин зүйлийн хэмжээг тус тус ЭЛИЗА-ийн аргаар тодорхойлоход фосфатын буферт хандлан гомогенжүүлж, этанолоор тундасжуулсан болон нэрмэл усаар хандлан гомогенжүүлээд ацетоноор тундасжуулсан хувилбаруудад эхсийн 13-р уураг 34.4±9.2 ба 34.9±1.3 пг/мл, өсөлтийн хүчин зүйл 469.4±46.9 ба 404.7±153.9 пг/мл хэмжээтэй байгаа нь фосфатын буфер эсвэл нэрмэл усанд хандлан, гомогенжүүлж, органик уусгагчдаар тундасжуулах замаар биологийн идэвхт уураг илүү их агуулсан ханд бэлтгэх боломжтойг харуулж байна. Түлхүүр үг: Адуу, судаслаг бүрхүүл, 13-р уураг, өсөлтийн хүчин зүйл, тунадасжуулалт,